Civic Education in Organizing Good Citizenship in Junior High School - Devita Kusuma Pratiwi; Mufidah Nur Faizah; Suparmi (Manajia: Journal of Education and Management, 2026)
This literature study aims to encourage and improve the understanding of Civic Education in regulating and realizing Good Citizenship among junior high school students. Good Citizenship is defined comprehensively, covering Civic Knowledge, Civic Skills, and Civic Disposition, as well as covering the main objectives of national education based on Pancasila. The results of this study show that Civic Education plays a crucial role in shaping Good Citizenship, encouraging independence in learning, and instilling social values based on Pancasila. The implementation of Civic Education must be comprehensive and contextual, emphasizing practical aspects such as the development of critical and rational thinking and psychomotor aspects. However, this literature study found many gaps in implementation, where learning methods and school environmental factors need to be optimized through a modern approach, one of which is based on the current curriculum, with the hope of producing intelligent, moral students who are actively involved in participating in social and national life.